1993
DOI: 10.1159/000196198
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Endotracheal Polyp Resolved after Antibiotic Treatment

Abstract: We describe a rare case of asymptomatic inflammatory endotracheal polyp resolved by antibiotic treatment. Histological examination of biopsy specimens showed an inflammatory polyp consisting of fibrovascular stroma and sparse lymphocyte infiltration. The size of the polyp was unchanged during 3 months without any treatment and its etiology was unclear. Although a bacterial organism was never proven, the polyp decreased remarkably under treatment with an oral antibiotic (ciprofloxacin) and did not recur for 6 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Several chronic inflammatory etiologic factors, such as chronic smoke inhalation, chronic inflammation in patients with asthma and chronic obstructive pulmonary disease (COPD), repeated airway infections, foreign body aspiration and prolonged mechanical ventilation may be potential causes. Yamagishi et al described a case of polyps that were resolved with antibiotic treatment (14). Consequently, our patient was treated with low-dose glucocorticoids and azithromycin for three months.…”
Section: Discussionmentioning
confidence: 88%
“…Several chronic inflammatory etiologic factors, such as chronic smoke inhalation, chronic inflammation in patients with asthma and chronic obstructive pulmonary disease (COPD), repeated airway infections, foreign body aspiration and prolonged mechanical ventilation may be potential causes. Yamagishi et al described a case of polyps that were resolved with antibiotic treatment (14). Consequently, our patient was treated with low-dose glucocorticoids and azithromycin for three months.…”
Section: Discussionmentioning
confidence: 88%
“…Tracheobronchial inflammatory polyps in man have been classified into 3 categories: 1) benign inflammatory polyps; 2) multiple papillomatosis; and 3) solitary papillomas. The latter 2 categories have malignant potential (Yamagishi et al 1993). The polyp described in this report would be classified in the first category.…”
Section: Discussionmentioning
confidence: 87%
“…Still, there has been no guideline or randomized controlled trial regarding the treatment of inflammatory polyp, but some previous cases have reported reduction in the size after use of antibiotics, steroids, and intervention . Antibiotics and steroids were used in our cases as we assumed EBUS‐TBNA might have caused mucosal disruption with infection which resulted in inflammatory process.…”
Section: Discussionmentioning
confidence: 92%